Evaluation of the CGIAR Research Program “Policies, Institutions and Markets” (PIM) - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
During the period under review (2012– 2014), the program was organized into seven flagships that conducted research from the global to the local level, and an eighth cross - cutting flagship on gender, partnerships, and capacity strengthening. Each flagship has established its own intermediate development outcomes (IDOs) which collectively constitute the specific objectives of the program (Table 1 in Chapter 2).